SOSIALISASI MITIGASI BENCANA BERBASIS PERKOTAAN DI KOTA MAKASSAR (PENDIDIKAN DAN LATIHAN WATER RESCUE DAN MANAJEMEN BENCANA) - Jusman, Jusman; Rijal, Rijal; Mappiwali, Hermawati; Rahman, Abd; Syamel, Sitti Sahara; Faisal, Muh. (Jurnal Abdimas Bina Bangsa, 2025)
The initiative to socialize urban disaster preparedness in Makassar City involves educational and training programs focused on water rescue and disaster management, with the goal of enhancing the community's readiness to confront various disaster risks, particularly floods, tornadoes, droughts, and fires. To achieve this, the program was executed in partnership with the Makassar City Regional Disaster Management Agency (BPBD), aiming to provide socialization and training for 50 participants, including community members, youth, and students. This endeavor sought to equip the community with essential knowledge and practical skills necessary for emergency response and evacuation in the event of a disaster.Through this socialization effort, the expectation is that the community will develop a deeper understanding of the significance of collaboration in mitigating disasters, thereby becoming more prepared to implement preventive measures against disaster threats within their surroundings. The outcomes of this program indicate an enhancement in the community’s knowledge and skills regarding disaster mitigation, which is a crucial initial step towards fostering greater resilience against disaster risks in urban settings.